Keabsahan dan Akibat Hukum Perjanjian Kawin Selama Masa Perkawinan Terhadap Harta Bersama Pasca Perceraian (Studi Kasus Putusan Nomor 294/PDT/2022/PT.DKI) - Amanda Fitra Hamzah; Margaretha Shintauli; Junita Marsyabillah; Muhammad Farrel Radithyo (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Constitutional Court Decision Number 69/PUU-XIII/2015 broadened the timeframe for concluding a marriage agreement so that it may be made during marriage, yet did not eliminate its validity requirements under the Civil Code. This study analyzes the legal position of marriage agreements made during marriage and their legal consequences for the division of joint marital property after divorce, based on a case study of the Jakarta High Court Decision Number 294/PDT/2022/PT.DKI using a normative legal method. The findings show that a marriage agreement made during marriage is valid but conditional, and its legal effect is prospective, so that where the agreement is declared invalid, the status of the property reverts to the joint marital property provisions.